2001
DOI: 10.1002/arch.1047
|View full text |Cite
|
Sign up to set email alerts
|

Captopril, a specific inhibitor of angiotensin converting enzyme, enhances both trypsin and vitellogenin titers in the grey fleshflyNeobellieria bullata

Abstract: A strong and constitutive angiotensin converting enzyme- or ACE-like activity was demonstrated in the hemolymph of the adult grey fleshfly Neobellieria bullata. In a competition assay, the N. bullata trypsin modulating oostatic factor (Neb-TMOF) was confirmed to be an in vitro substrate for this circulating Neb-ACE. Oral uptake of captopril, a selective and specific inhibitor of ACE, resulted in a complete phenotypic knockout of circulating ACE activity. When compared with control animals, captopril-fed female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
3
21
1
Order By: Relevance
“…Since Neb-TMOF is an in vivo substrate for Neb-ACE, the captopril treatment had a direct effect on trypsin activity and vitellogenin concentrations. Vandingenen et al (2001) also reported that captopril fed to female flies caused an increase in the liver meal-induced trypsin peak in the midgut and elevated levels of protein-induced yolk polypeptides in the hemolymph, but oocyte growth was not affected.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since Neb-TMOF is an in vivo substrate for Neb-ACE, the captopril treatment had a direct effect on trypsin activity and vitellogenin concentrations. Vandingenen et al (2001) also reported that captopril fed to female flies caused an increase in the liver meal-induced trypsin peak in the midgut and elevated levels of protein-induced yolk polypeptides in the hemolymph, but oocyte growth was not affected.…”
Section: Introductionmentioning
confidence: 93%
“…Females that had been mated with these ACE-inhibited males showed a dramatic reduction in fecundity (Ekbote et al, 2003a). In addition, Vandingenen et al (2001Vandingenen et al ( , 2002 treated female adults of the grey fleshfly Neobellieria bullata with captopril and studied the in vivo relationship between Neb-TMOF (trypsin modulating oostatic factor) and Neb-ACE. Since Neb-TMOF is an in vivo substrate for Neb-ACE, the captopril treatment had a direct effect on trypsin activity and vitellogenin concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with the general tissue distribu tion of ACE in insects. Although this distribution is not identical in different species, ACE seems to be concen trated in certain tissues, including reproductive tissues, brain, midgut and hemolymph (Cornell et al, 1995;Ekbote et al, 1999;Vandingenen et al, 2001;Vandingenen et al, 2002), suggesting that the enzyme is of physiological importance in these tissues. Indeed, numerous reports substantiate the involvement of insect ACE in reproduction, pro-hormone processing and regu lation of peptide titers (Isaac et al, 1994;Tatei et al, 1995;Wijffels et al, 1996;Lamango et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…ACE activity measurements were based on the method pro posed by Ryan et al (1977) and modified as in Vandingenen et al (2001). Typically, reactions were conducted in a final volume of 100 pl in HEPES (see above) buffer.…”
Section: Ace Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation